Monitoring system for sustainable tourism in Swiss Alpine Regions. Tools for regions to act on their own initiative - Klaus-Dieter Schnell; Anja Umbach-Daniel; Julia Johnsen (European Regional Science Association (ERSA), 2003)
Sustainability in the different spheres of ecology, society and economy of alpine regions is essential for cultural and landscape preservation as well as for ongoing development. Particular attention must be paid to regional economy development and the role of tourism. In many alpine regions tourism is a very important economic factor to the local people, and may even be the only source of primary income from outside the region. It is assumed that the importance of tourism for economic development in the alpine regions will increase in future. Theories about regional sustainable development state, the regional level (or destination level as to say in tourism) is dedicated to conjoin the global concept of sustainable development and the intention of putting it into action. The first section of the paper summarises basic definitions of sustainability and sustainable tourism. It derives some basic assumptions for the operationalisation of sustainable regional development and the role of tourism. A survey on current trends in tourism development of alpine regions is given. The second section describes the prerequisites for a tool, which helps regions to monitor and to manage their own development in a more sustainable direction. A coherent framework for an indicator system for sustainable tourism development is derived from existing theories and definitions of sustainability as well as from a model which describes mechanism and interactions in the system of tourism development in alpine regions. Therefrom, a systematic model for the identification of indicators for sustainable tourism development is established, drawing upon state of the art theories about sustainability indicators. The third section describes three different levels for the monitoring of sustainability in tourism development: a) the monitoring of the status of a region concerning sustainable regional and tourism development, b) the reflection of the processes which enable a region's sustainable development and c) the assessment of touristic projects or programmes, which are designated to achieve specific regional goals or to foster sustainable regional development in general. This threesome structure ensures the multiple usability of the indicator set by a region. How the potential users, e.g. regional authorities or tourism bodies, assess the usability of the basis indicator set in reality, is described by means of a first testing phase in Swiss alpine regions, which has started in 2003. This research takes part in the framework of Swiss National Research Programme 48 ?Landscapes and habitats of the alps'. Finally, a conclusion is drawn on the usefulness of such a monitoring and management system for sustainable tourism.
Keywords: 330